On the issue of establishment and changes of boundaries of administrative and territorial units - Kharytonenko, R.; Derkulskyi, R.; Kravchenko, O.; Smolenskyi, V. (Land Management, Cadastre and Land Monitoring, 2021)
Scientific approaches to establishing and changing the boundaries of administrative-territorial units are analyzed. It is noted that the share of established and changed boundaries of settlements is over 73%. The actual level of the boundaries of settlements entered into the information of the State Land Cadastre is 32%, which indicates a significant number of administrative-territorial units whose boundaries are not established. This makes it impossible to achieve the goals of development of territories of both settlements and territorial communities. Given that the boundaries of most settlements and territorial communities are not established, and when they change there are issues that can not be resolved under the existing system of legal documents and scientifically justify their establishment or change, which negatively affects community regulation of environmental and economically acceptable land use. The following changes to the normative legal documents are proposed: to provide for preliminary registration in the SCC of the project boundaries of the territories of settlements and territorial communities; create opportunities to check the XML exchange file to establish (change) the boundaries of administrative-territorial units; establishment (change) of borders should be carried out taking into account the principles of "public administration" (especially self-organization of civil society). Key words: administrative-territorial unit, boundary of territorial community, boundary of settlement, State land cadastre.